Research On Websites Of 43 Publıc Relations Agency Members Of Public Relations Society Of Turkey (Tühid) In Aspect Of Public Relations - Aydınalp - Ilıcak, Ş. Güzin (The Turkish Online Journal of Design, Art and Communication, 2012)
Nowadays public relations studies have entered a more effective process via recent media tools. In this study, the websites of 43 public relations agency members of Public Relations Society of Turkey (TÜHİD) are being evaluated in aspect of public relations. When considered from this point of view, the websites of the agencies in question have been analyzed in terms of company information, communication attempts, media relations, corporate identity, corporate publications and interaction. The study has been designed using content analysis method of qualitative research methodology to research the websites of aforesaid 43 public relations agencies. Since the websites of 12 agencies are under construction, the rest 31 websites have been taken under review. The data obtained from this study has revealed to what extent the websites of public relations agencies are being appropriately and effectively used in terms of public relations techniques.
Keywords: Websites; Public Relations Agency; TÜHİD; Public Relations Techniques; Web Siteleri; Halkla İlişkiler Ajansı; Halkla İlişkiler Teknikleri